1994
DOI: 10.1111/j.1651-2227.1994.tb12957.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of cadaver kidney transplantation in small children

Abstract: Small children have often been reported to have poor outcome after kidney transplantation (KT). Recent reports from North America have shown that the use of living-related donors improves patient and graft survival. We report the experience in one centre of primary cadaveric KT using sequential immunosuppression in nine children aged 8-30 months and weighing 5.4-9.8 kg; donors were 0.7-12.3 years old. Four patients had pre-emptive KT and the other five were on peritoneal dialysis; the mean +/- SD waiting time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…We believe that our data support those of Gellermann et al [1] in suggesting that ABPM on pre-school children is feasible, and therefore may become a useful tool in this age group. The potential of the technique cannot however be fully realised in the absence of reliable normative data.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…We believe that our data support those of Gellermann et al [1] in suggesting that ABPM on pre-school children is feasible, and therefore may become a useful tool in this age group. The potential of the technique cannot however be fully realised in the absence of reliable normative data.…”
supporting
confidence: 89%
“…The potential of the technique cannot however be fully realised in the absence of reliable normative data. Further studies are needed to test our observations and those of Gellermann et al [1] in other preschool children and to generate age-specific population data.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…All the recipients received rabbit anti-thymocyte globulins, azathioprine, prednisone, and delayed cyclosporin A [7].…”
Section: Methodsmentioning
confidence: 99%
“…42-44,47,4s Cochat et al reported that infants who received cadaveric grafts obtained as good a result as those with living-related donors. 49 In most centers, early graft losses due to patient death were the largest risk factor in both patients and graft survival. If early graft loss due to death was not calculated in the survival data, the patient and graft survival rates for infants would be better than those for older age groups.…”
Section: Mortality Ratesmentioning
confidence: 99%